Uncialamycin as a novel payload for antibody drug conjugate (ADC) based targeted cancer therapy. Issue 3 (1st February 2019) - Chowdari, Naidu S.; Pan, Chin; Rao, Chetana; Langley, David R.; Sivaprakasam, Prasanna; Sufi, Bilal; Derwin, Daniel; Wang, Yichong; Kwok, Eilene; Passmore, David; Rangan, Vangipuram S.; Deshpande, Shrikant; et al.
Graphical abstract: Abstract: Uncialamycin analogs were evaluated as potential cytotoxic agents in an antibody-drug conjugate (ADC) approach to treating human cancer. These analogs were synthesized using Hauser annulations of substituted phthalides as a key step. A highly potent uncialamycin analog 3c with a valine-citrulline dipeptide linker was conjugated to an anti-mesothelin monoclonal antibody (mAb) through lysines to generate a meso -13 conjugate. This conjugate demonstrated subnanomolar potency (IC50 = 0.88 nM, H226 cell line) in in vitro cytotoxicity experiments with good immunological specificity to mesothelin-positive lung cancer cell lines. The potency and mechanism of action of this uncialamycin class of enediyne antitumor antibiotics make them attractive payloads in ADC-based cancer therapy.